A locus for spondylocarpotarsal synostosis syndrome at chromosome 3p14. Issue 4 (1st April 2004) - Steiner, C; Ehtesham, N; Taylor, K D; Sebald, E; Cantor, R; King, L M; Guo, X; Hang, T; Hu, M S; Cui, J-R; Friedman, B; Norato, D; et al.
Abstract : Spondylocarpotarsal synostosis syndrome is a rare autosomal recessive disorder characterised by vertebral fusions, frequently manifesting as an unsegmented vertebral bar, as well as fusions of the carpal and tarsal bones. In a study of three consanguineous families and one non-consanguineous family, linkage analysis was used to establish the chromosomal location of the disease gene. Linkage analysis localised the disease gene to chromosome 3p14. A maximum lod score of 6.49 (q = 0) was obtained for the marker at locus D3S3532 on chromosome 3p. Recombination mapping narrowed the linked region to the 5.7 cM genetic interval between the markers at loci D3S3724 and D3S1300. A common region of homozygosity was found between the markers at loci D3S3724 and D3S1300, defining a physical interval of approximately 4 million base pairs likely to contain the disease gene. Identification of the gene responsible for this disorder will provide insight into the genes that play a role in the formation of the vertebral column and joints.